TREND ANALYSIS OF FINANCIAL RATIOS FOR ASSESSMENT FINANCIAL STABILITY LONG-TERM ON PT AGUNG PODOMORO LAND TBK - Hardiyanti, Siti Epa; Arthawati, Sri Ndaru (Management Science Research Journal, 2025)
This study aims to evaluate the long-term financial stability of PT Agung Podomoro Land Tbk by analyzing the trends in its financial ratios over the period 2018–2024. As a leading real estate developer in Indonesia, the company faces financial challenges that require consistent monitoring, especially considering macroeconomic fluctuations and sector-specific risks. The research employs trend analysis of key financial ratios, including liquidity, solvency, profitability, and efficiency indicators. The results show notable fluctuations influenced by the COVID-19 pandemic and post-pandemic recovery phases. The study concludes that while the company demonstrates signs of improvement in operational efficiency and profitability, concerns remain regarding solvency and capital structure. The findings provide valuable insights for management, investors, and financial analysts regarding the company’s long-term financial health.